Two new shaped coal pillars designed to protect the subsurface pipeline in the gas-coal integrated mining field - Zhao, Yixin; Ren, Jiandong; Sun, Zhongbo (International journal of mining science and technology, 2025)
In the gas-coal integrated mining field, the conventional design method of pipeline coal pillars leads to a large amount of coal pillars being unrecovered and overlooks the pipeline’s safety requirements. Considering the coal pillar recovery rate and pipeline’s safety requirements, two new shaped coal pillar design approaches for subsurface pipelines were developed. Firstly, the deformation limitations for measuring pipeline safety are categorized into two: no deformation is permitted, and deformation is acceptable within elastic limits. Subsequently, integrating the key stratum theory (KST) and cave angle, a fishbone-shaped coal pillar design approach that does not permit pipeline deformation is established. Meanwhile, combined with the ground subsidence and the pipeline’s elastic deformation limit, a grille-shaped coal pillar design approach that accepts deformation pipelines within elastic limits is established. Those two new approaches clarify parameters including mined width, coal pillar width and mined length. Finally, the case study shows that the designed mined width, coal pillar width and mined length of the fishbone-shaped coal pillar are 90, 80, and 130 m, while those of the grille-shaped are 320, 370, and 640 m. Compared with the conventional method, the fishbone-shaped and grille-shaped coal pillar design approaches recovered coal pillar resources of 2.65×106 and 5.81×106 t on the premise of meeting the pipeline safety requirements, and the recovery rates increased by 20.5% and 45.0%, with expenditures representing only 56.46% and 20.02% of the respective benefits. These new approaches provide managers with diverse options for protecting pipeline safety while promoting coal pillar recovery, which is conducive to the harmonic mining of gas-coal resources.